Book review: Davidson, Paul (2011): Post Keynesian Macroeconomic Theory: A Foundation for Successful Economic Policies for the Twenty-First Century, 2nd Edition, Cheltenham, UK (360 pages, paperback, Edward Elgar, ISBN 978-1-84980-980-1) - Achim Truger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
The publishing of a second edition of a macroeconomic textbook 17 years after the first edition is not an event that usually receives great attention – even if the subtitle promises that a 'foundation for successful economic policies for the twenty-first century' will be delivered. The second edition of Paul Davidson's textbook, Post Keynesian Macroeconomic Theory, however, should be an exception to the rule for at least three reasons.
Keywords: 330